Morphologic characterization and evaluation of the productivity of nine rootstocks of rose bush (rosa spp.) - Pivetta, K. F L [UNESP]; Pizetta, P. U C [UNESP]; Pedrinho, D. R. [UNESP] (My University, 2004)
In Brazil, garden and cut rose bushes are propagated through cuttings or grafting. The rootstocks used in most of the traditional areas of cultivation are not identified, being known just by the vulgar name. There is not any information in the literature on the morphologic characteristics, nor about the productivity of different cultivars on the rootstocks available in Brazil. The objective of this work was to characterize and determine productivity of nine rootstocks (Rosa multiflora 'Paulista'; R. multiflora 'Japones'; R. multiflora 'Iowa'; R. multiflora 'Kopmans'; R. indica 'Mayor'; R. indica x multiflora; R. sp. 'Natual Brier'; R. manetti and R. canina 'Inermis') grafted with 'Versilia' and 'Tineke' scions. Morphologic studies were undertaken to characterize branches of adult plants to determine shape and dimensions of the leaf; number of prickles/15 cm of stem; vigor of the stems; incidence of Diplocarpon rosae (blackspot) and coloration of the leaf. The productivity (number of commercial flowers/plant/month) was evaluated for 6 months (October, 2000 to March, 2001), in the city of Andradas, Minas Gerais State, located at 1251 meters above sea level. Since there was significant difference in just two months for both rootstocks, 'Tineke' and 'Versilia', no rootstocks could be considered inadequate. Nonetheless, in general, the rootstocks that showed a better performance with 'Tineke' were, R. multiflora 'Kopmans' and R. manetti and with 'Versilia', R. multiflora 'Kopmans' and Rosa sp. 'Natual Brier'.
Keywords: Grafting; Morphology; Production